Perfil dos cursos de formação de professores dos programas de licenciatura em química das instituições públicas de ensino superior da região nordeste do Brasil - Marques, Clara Virginia Vieira Carvalho Oliveira (Universidade Federal de São Carlos, 2010)
This study aimed to determine the profile of Chemistry´s courses of Public Institutions of higher education in Brazilian Northeastern, referencing the current educational paradigms and also the legal guidelines regarding processes teacher training governed by the Brazilian education. We attempted to trace the identity of these courses through the perspectives of the adequacy of legal issues and adequacy of the regional reality, understanding the concepts and interactions between faculty and students in the process of training teachers of Chemistry. The methodology was based on the qualitative research structuration, using documentary analysis and content analysis of semi-structured interviews and questionnaires, which were treated under the scheme of the methodology of systemic networks. We studied the Political Pedagogical Project and the Curriculum Matrix for 16 courses in Chemistry from the Northeast, as well as the content analysis of interviews with coordinators and teachers and questionnaires to a graduating students sample. The results showed that the courses are seeking to effect their adequacy, however, was identified a marked segmentation between the training areas of chemical knowledge and pedagogical and still prevailing the model of teacher training based on technical rationality. The Internship and Supervised Practice Component Course as were the dimensions that showed the greatest inconsistencies in the change process suggested by current law. Therefore, the profile of studied courses is not yet equal to that recommended in the new Brazilian education paradigms for teacher training.
Keywords: Química; Educação - formação; Currículos - mudança; Política educacional; Professor reflexivo; Chemistry; Education; Educational policy; CIENCIAS EXATAS E DA TERRA::QUIMICA